Informacijsko inženjerstvo kao metodološka postavka u razvoju životnog ciklusa informacijskih sustava - Rotim, Franko; Grbavac, Vitomir (Promet - Traffic&Transportation, 2012)
In past decades data processing in corporations has been looking order and integration so that some major success could be expected only with the improvement and refinement of software instruments. Nowadays we have available procedures which make it possible for us to create better programs. These are: application generators, languages of the fourth generation, and inspection languages, in conjunction with some other instruments. However the fact is that up to this point of time computer ·data processing has generated numerous inadequately structured programs and incompatible data banks with reference to the application autonomy. In such conditions changes of the user’s requirements and demands have often caused changes to the data models which have then in turn affected adversely the overall application. Preventing this adverse impact could be materialized only through a very strict, discipline oriented and slow procedure. The resolution of this issue rests in the strategic planning of information resources required for operations of a concrete business organization. Therefore the models of data represent stable basis on which procedures are established in a well-organized and managed data processing. In fact they represent the link between the entities composed of attributes. The combination of entities and attributes a dually makes the basis for future data processing. It is further possible by making use of modern software instruments for management of software instruments data banks to add new entities and attributes without the known difficulties. In the light of the above this paper deals. With the information engineering as a series of disciplines required for the construction of computerized organization based upon an integrated system for data bank management. The basic prerequisite of information engineering is that the data are stored and that they are maintained by different types of software system of data. Therefore the construction of blocks of information engineering must be available in conjunction with modern techniques of development. The fact is that it represents a great challenge to structure a data system without basic blocks of information engineering because - structuring a modern data processing system without basic blocks of information engineering is equal to building castles in the sand.